Neutron noise modelling for nuclear reactor diagnostics - Mylonakis, A.; Vinai, P.; Demaziére, C. (HNPS Advances in Nuclear Physics, 2019)
This paper presents the development of a neutron noise simulator for fine-mesh applications.The neutron noise of power nuclear reactors deals with the fluctuations of the neutron flux that are induced by fluctuations or oscillations of the reactor properties, i.e. displacement of core components, temperature or density variations, etc. Since the appearance of these perturbations can be problematic for the operation of nuclear reactors, it is desirable to be able to analyze their possible effects. The comparison between the modelling of such perturbations and possible measurements also gives the possibility to determine the driving perturbation in an operating nuclear reactor. One modelling approach is to solve numerically the neutron noise diffusion equation. This paper presents CORE SIM+, an under-development numerical tool oriented to neutron noise problems that require the fine-mesh spatial discretization of the reactor core.